Pengaruh Harga dan Inovasi Produk terhadap Pembelian Unit Sepeda Motor pada Dealer Yamaha - Dama Irfansyah; Eti Rochaeti (Neolectura, 2022)
This study aims to find the effect of price and innovation of a product that is determined by the manufacturer on consumer decisions in buying Yamaha motorbikes at the Amie Jaya Motor Depok Dealer. This research method is quantitative. The independent variable is product innovation (X1), price (X2) and the dependent variable is the purchase decision (Y). The population in this study were dealer consumers who transacted in the last three months at Yamaha Amie Jaya Motor Depok, 179 of whom were taken. Of these, a sample is needed to describe the condition of the population based on Slovin's calculations, namely 124 people. The results of the study show that the price and product innovation determined by the manufacturer have a significant influence on the consumer's decision to buy a motorbike. The magnitude of the influence of product innovation and price variables has a determination of 49%, while 51%. Product innovation is the variable that has the greatest significance for the consumer's decision to buy a motorcycle compared to the manufacturer's pricing